The influence of powdery mildew (Erysiphe graminisf.sp.hordei) on the accumulation of transcripts from low-temperature-responsive genes in barley - O'Hara, P; Ayres, P.G; Hughes, M.A; Dunn, M.A; Smith, R.J (Physiological and molecular plant pathology, 1998)
Members of two barley gene families,blt4 andblt101, previously shown to be upregulated in winter cultivar Igri by a period of low temperature treatment, responded to challenge and infection byErysiphe graminisf.sp.hordei. There was at normal temperature a transient and modest increase in transcript accumulation ofblt4 genes in shoots and leaves within hours of inoculation. When plants with established infections were transferred to low temperature, transcription ofblt4 andblt101, in leaves and shoots, was less than that in uninfected plants. The degree of inhibition of transcript accumulation in both leaves and shoots was positively related to the area of leaf inoculated and was weakest, but detectable, in uninoculated tissues. Infected plants subject to a freezing and regrowth test showed no significantly increased susceptibility to freezing injury compared to non-infected plants. Survivors and non survivors of this test showed no significant difference in transcript accumulation of these genes in leaves harvested immediately prior to the test.